Blotches on the sunflower - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Late in 2001, the Association for Strengthening Agricultural Research in Eastern and Central Africa reported a new viral disease in sunflowers, found in Kenya, Malawi, Tanzania and Zambia, causing leaves to crinkle and in cases of severe...